Concepts of combinatorial optimization - Paschos, Vangelis Th. (Hoboken : Wiley, 2014)
Combinatorial optimization is a multidisciplinary scientific area, lying in the interface of three major scientific domains: mathematics, theoretical computer science and management. The three volumes of the Combinatorial Optimization series aim to cover a wide range of topics in this area. These topics also deal with fundamental notions and approaches as with several classical applications of combinatorial optimization. Concepts of Combinatorial Optimization, is divided into three parts:- On the complexity of combinatorial optimization problems, presenting basics abo.
4.5.2. Backward procedure4.5.3. Principles of optimality and monotonicity; 4.6. Solution of the examples; 4.6.1. Stock management; 4.6.2. Shortest path bottleneck; 4.6.3. Knapsack; 4.7. A few extensions; 4.7.1. Partial order and multicriteria optimization; 4.7.1.1. New formulation of the problem; 4.7.1.2. Solution; 4.7.1.3. Examples; 4.7.2. Dynamic programming with variables; 4.7.2.1. Sequential decision problems under uncertainty; 4.7.2.2. Solution; 4.7.2.3. Example; 4.7.3. Generalized dynamic programming; 4.8. Conclusion; 4.9. Bibliography; PART III: Elements from MathematicalProgramming.
Chapter 5: Mixed Integer Linear Programming Models forCombinatorial Optimization Problems.
Print version record.
Keywords: Combinatorial optimization; Programming (Mathematics); MATHEMATICS -- Applied; MATHEMATICS -- Probability & Statistics -- General; Combinatorial optimization; Programming (Mathematics); Kombinatorische Optimierung; Electronic books